Validity Test on Scientific Approach based Hand out Teaching Materials of the Property and Volume of Three Dimensional Shape for Elementary School Students’ Grade V - Hasmawati K, Agustan Syamsuddin, Irwan Akib (International Journal of Advanced Science and Technology, 2020)
This research aims to determine the feasibility of teaching materials developed, which are hand-out teaching materials based on scientific approaches. Feasibility for learning devices is based on expert validation results. The teaching materials developed in this research were using a 4-D development model that consists of four stages namely 1) definition; 2) design; 3) development and 4) dissiminate that refer to the expert judgment. The instrument used was a validation sheet. Data from validation sheets were analyzed in a descriptive quantitative and qualitative descriptive. The study involved 4 validators, 2 lecturers and 2 elementary teachers grade V. Evaluation aspect of developed hand out are (1) material aspects consist of content, alignment, technique and use of language; (2) the design aspect consists of simplicity, alignment, balance, shape and color use. Based on the validity test results of the mathematical hand out, carried out an overview (1) on the material aspect acquired the average score of validator assessment 3.2 with a valid category, (2) on the design aspect, acquired the average scoring score of the validator by 3.1 with valid categories. Based on the validity analysis results of the scientific approach based hand out teaching material materials obtained an average score of 3.15 that is in the valid category, thus it can be used as one of the teaching materials in mathematics learning for students’ grade V of elementary school. Keywords: validity, hand out teaching material, scientific approach